The Political and Civic Implications of Chicago's Unsuccessful Bid to Host the 2016 Olympic Games. (November 2013) - Bennett, Larry; Bennett, Michael; Alexander, Stephen; Persky, Joseph
Between 2006 and 2009, Chicago's political and civic leadership developed a bid to host the 2016 Olympic Games. The International Olympic Committee (IOC) ultimately selected Rio de Janeiro to host the 2016 Games, with Chicago finishing fourth among the finalist cities in the October, 2009, IOC voting. This article is based on 20 key informant interviews with members and staff of the Chicago 2016 Committee, neighborhood activists and organizational staff in projected Olympic "venue" neighborhoods, and three "unaffiliated" civic leaders. The aim of the interviews was to determine—in light of the failed 2016 Olympic bid—if Chicago's leadership had effected a process of what urban regime theorists term "social learning, " collective retrospection that can lead to the pursuit of more successful future civic ventures. The evidence provided by these interviews suggests that not only has there been little civic retrospection by Chicago's leadership, but also that processes put in place to promote the Chicago bid to international and local constituencies actually inhibited the ability of local elites to learn from past action.